Context-aware based alert system for people with hearing impairments - Abbas, M.K. (Medwell Journals, 2018)
People with Hearing Impairments (PHIs) face challenges every day in identifying sounds like a visitor pressing the doorbell. The traditional doorbell uses an audio signal to notify people. However, it may not be able to notify PHIs because PHIs are very insensitive to sound. Due to the lack of help from support services, PHIs may not have normal daily lives. Therefore, it is necessary to propose an efficient doorbell solution in helping PHIs to be notified and the intangible benefit for PHIs is that it will reduce their dependency on their families in their daily lives. The proposed context-aware alert system would notify PHIs by using visual communication signals and tactile cues instead audio signals. Compared with the existing solution, the face recognition feature was added into the proposed system design and the system has become smart enough to know when the visitor's image has to be snapped and how to reduce the transmission time of the image. In addition what is context aware and how the context aware feature will benefit the system design will also be discussed. On the other hand, the intangible benefit of this research would be helping PHIs by reducing their dependency on others and building their self-confidence. Â© 2018, Medwell Journals.